Comparison of the incidence of acute kidney injury during treatment with vancomycin in combination with piperacillin-tazobactam or with meropenem - Majed S. Al Yami (Elsevier, 2017)
The purpose of this study was to evaluate the observed incidence of acute kidney injury (AKI) in adult patients receiving either piperacillin-tazobactam (PT) and vancomycin or meropenem and vancomycin for at least 48 h. In this retrospective cohort study, we included adult patients with no known renal dysfunction who received either the combination of PT-vancomycin or meropenem-vancomycin for at least 48 h. The study's primary outcome was the incidence of acute kidney injury (AKI), defined by the Kidney Disease: Improving Global Outcomes (KDIGO) in patients with baseline normal renal function as an increase in serum creatinine (Scr) by ≥0.3 mg/dl within 48 h. A total of 183 patients were evaluated for AKI. The incidence of AKI was higher but not statistically different in the PT-vancomycin group (7.41%) compared with the meropenem-vancomycin group (5.33%). This study was not able to detect a statistically significant difference in AKI between the two treatment groups. A larger prospective study is warranted. Keywords: Acute kidney injury, Nephrotoxicity, Vancomycin, Piperacillin-tazobactam, Meropenem